2000
DOI: 10.1093/emboj/19.15.4046
|View full text |Cite
|
Sign up to set email alerts
|

FIZZ1, a novel cysteine-rich secreted protein associated with pulmonary inflammation, defines a new gene family

Abstract: Bronchoalveolar lavage fluid from mice with experimentally induced allergic pulmonary inflammation contains a novel 9.4 kDa cysteine‐rich secreted protein, FIZZ1 (found in inflammatory zone). Murine (m) FIZZ1 is the founding member of a new gene family including two other murine genes expressed, respectively, in intestinal crypt epithelium and white adipose tissue, and two related human genes. In control mice, FIZZ1 mRNA and protein expression occur at low levels in a subset of bronchial epithelial cells and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
561
2
14

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 605 publications
(619 citation statements)
references
References 32 publications
35
561
2
14
Order By: Relevance
“…A third group initially found resistin, which they named 'FIZZ3', as an expressed sequence tag related to a protein they found to be induced during lung inflammation known as 'found in inflammatory zone 1'. 58 Resistin is a 12.5 kDa cysteine-rich, C-terminal protein, whose mRNA expression has been predominantly observed in white adipose tissue, and to a lesser extent in the hypothalamus, the pituitary, BAT, the stomach, the large intestine, the adrenal gland and skeletal muscles, in rats. [59][60][61] In vitro studies showed that resistin is induced during adipocyte differentiation 53,57,62 and, as suggested by its signal sequence, is secreted into the media.…”
Section: Resistinmentioning
confidence: 99%
“…A third group initially found resistin, which they named 'FIZZ3', as an expressed sequence tag related to a protein they found to be induced during lung inflammation known as 'found in inflammatory zone 1'. 58 Resistin is a 12.5 kDa cysteine-rich, C-terminal protein, whose mRNA expression has been predominantly observed in white adipose tissue, and to a lesser extent in the hypothalamus, the pituitary, BAT, the stomach, the large intestine, the adrenal gland and skeletal muscles, in rats. [59][60][61] In vitro studies showed that resistin is induced during adipocyte differentiation 53,57,62 and, as suggested by its signal sequence, is secreted into the media.…”
Section: Resistinmentioning
confidence: 99%
“…Resistin is a cysteine-rich secretory polypeptide expressed in adipocytes and belongs to a protein family called resistinlike molecules, which is also known as the found-in-inflammatory-zone family [1][2][3]. Resistin has been proposed as a potential link between obesity and insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of resistin increases with increasing mass of adipose tissue. The resistin gene is identical to the FIZZ3 gene discovered earlier by Holcomb et al (2000). Although there are several observations that are compatible with a role for resistin in the development of insulin resistance in rodents as well as in man, there are data that support the notion that the major function of resistin in man may be related to inflammation (Weisberg et al 2003).…”
Section: Resistinmentioning
confidence: 73%
“…Although there are several observations that are compatible with a role for resistin in the development of insulin resistance in rodents as well as in man, there are data that support the notion that the major function of resistin in man may be related to inflammation (Weisberg et al 2003). Resistin like other RELM proteins comprises 105-114 amino acids and is characterized by a specific pattern made up of ten cysteine residues (Holcomb et al 2000). It circulates in the plasma as a trimer or a hexamer (Patel et al 2004).…”
Section: Resistinmentioning
confidence: 99%
See 1 more Smart Citation